The Impact of Financial Literacy and Financial Technology on Financial Inclusion in Special Region of Yogyakarta, Indonesia - Kusumawati, Rita; Akmalia, Alien; Wardana, Candra Kusuma (Riviera Publishing, 2022)
Someone who has appropriate knowledge toward financial literacy (well literate) will be faster to learn about how financial institution works. Unfortunately, the level of financial literacy in Indonesia is only reached 29 percent. However, the goventment target on financial literacy itself is reached up to 75 percennt. Since the knowledge on how to manage the personal budget is quite important, people need to know to overcome the financial problem that could be occur in the future endeavors. This research aim to identificate the level of influence financial literacy toward financial inclusion in Special Region of Yogyakarta, Indonesia as part of the impact by financial technology usage. This study was used quantitative apprach using 133 respondents in Special Region of Yogyakarta. The data were obtained from spreading the questionnaire and interviews with respondents. Data analysis in this study used multiple linear regression using SPSS ver. 22. The result of this study shows that only financial technology which supported to influence financial Inclusion.